Studi Potensi Air Pada Pembangkit Listrik Tenaga Air (PLTA) Tabulahan - Sabrina, Dita; Faisal, Zulvyah; Taufik Iqbal, Muhammad; Aziz, Pratiwi; Minarni, Teti (Jurnal Teknik Mesin Sinergi, 2024)
This study analyzes the potential and operational planning of the Tabulahan hydropower plant located at the Bonehau River, Periangan Village, Tabulahan District, Mamasa Regency, West Sulawesi. The project utilizes a water catchment area of 306 km² upstream of the dam and 324 km² downstream of the plant. The discharge analysis uses the Flow Duration Curve (FDC) method with the results showing adequate discharge availability. A reliable discharge of 22.80 m³/s was selected based on a reliability level of 85%-90%, with a design discharge of 8.97 m³/s for each turbine. For further planning analysis, the power generation discharge was set at Q50% (14.72 m³/second) and the river maintenance discharge (ecoflow) at Q95% (21.60 m³/second). With an installed power capacity of 10 MW, the Tabulahan hydropower plant is designed to optimize the potential of water resources with a sustainable approach. Keywords: Reliable Discharge; Tabulahan Hydropower Plant; FDC Abstrak: Penelitian ini menganalisis potensi dan perencanaan operasional PLTA Tabulahan yang terletak di Sungai Bonehau, Desa Periangan, Kecamatan Tabulahan, Kabupaten Mamasa, Sulawesi Barat. Proyek ini memanfaatkan daerah tangkapan air seluas 306 km² di hulu bendungan dan 324 km² di hilir rumah pembangkit. Analisis debit menggunakan metode Flow Duration Curve (FDC) dengan hasil menunjukkan ketersediaan debit yang memadai. Debit andal sebesar 22,80 m³/detik dipilih berdasarkan tingkat keandalan 85%-90%, dengan debit desain masing-masing turbin sebesar 8,97 m³/detik. Untuk analisis perencanaan lebih lanjut, debit pembangkit ditetapkan pada Q50% (14,72 m³/detik) dan debit pemeliharaan sungai (ekoflow) pada Q95% (21,60 m³/detik). Dengan kapasitas daya terpasang sebesar 10 MW, PLTA Tabulahan dirancang untuk mengoptimalkan potensi sumber daya air dengan pendekatan berkelanjutan. Kata kunci : Debit Andal; PLTA Tabulahan; FDC